Fractionation of Hepatic Nonparenchymal Cells - John Graham (The Scientific World Journal)
The majority of parenchymal cells from mammalian liver cells can be removed by very low speed centrifugation (50 g) but a simple low-density barrier (1.096 g/ml) is required to remove the remaining parenchymal cells from the 50-g supernatant which contains all of the lower density nonparenchymal cells. Continuous gradients of Nycodenz® can provide satisfactory resolution of Kupffer, stellate, and endothelial cells on an analytical basis but the separation of different cell types is not sufficient preparatively. Flotation through a low-density iodixanol barrier can, however, provide a satisfactory enrichment of the least dense nonparenchymal cell – the stellate cells.